Replacement of Weathered Clay Shale Using Soil Cement for Bridge Approach Embankment in Purwakarta - Indonesia - Albert Johan; Andy Sugianto; Paulus Pramono Rahardjo (Indonesian Geotechnical Journal, 2023)
Clay shale is a sensitive soil material that easily experiences weathering if exposed to open air, sunlight, water. Weathered clay shale is commonly located near the surface and has a soft consistency due to surface water infiltration. Referring to this condition, weathered clay shale is prone to experience soil movement if backfill work is conducted on the top side of weathered clay shale material. Therefore, to minimize the potential of soil movement during backfilling, soil replacement using soil cement is recommended to be conducted to gain higher soil shear strength and to prevent excessive water infiltration to the fresh clay shale. To gain further understanding, a comprehensive study about the replacement of weathered clay shale using soil cement for bridge approach embankment in Purwakarta was carried out. This study comprises site observation, field data collection, laboratory test, explanation about implementation and quality control. The stages in implementation of soil cement is carried out in several stages such as : evaluation of soil condition on the project site, checking the suitability of local soil for the soil cement stabilization, conducting field test trial mockup followed by quality control, conducting crumb test and mechanical properties test for soil cement mixture. Based on assessment results, the soil cement mixture shall be directly compacted after the soil cement mixture is homogeneous to prevent segregation and shall be given a curing time of at least 3-7 days without additional water to gain better soil shear strength. Furthermore, according to the crumb test result, soil cement material was identified as quite impermeable which is verified by evidence that there was no significant change in water content and the soil cement sample could still stand firm after soaked for 7 days.